Observatory of Paraiba Media: Transforming the media for the debate and the criticism - S. Freires Aires, Janaine; Nunes Alves, Carlos Edmário (Guará Journal, 2015)
The project of education, research and extension “Observatório da Mídia Paraibana” was created in 2009 from a student initiative. On this occasion, we present the story of the proposal, its objectives, the methodology used and of the results. We seek, especially, talk about the performance of these tools in strengthening citizenship. “Observatório da Mídia Paraibana” is an instrument for strengthening the Human Right to Communication in Paraíba.
Keywords: Communication rights; Mediacriticismo; Paraíba